Preparation method of porous ceramic with uniform micro-nano aperture
The formation of micro-nanogel foams through micro-nano bubble generators and high-speed shearing technology solves the problems of low foam stability and large pore size in existing porous ceramic materials, and achieves the preparation of porous ceramic materials with small, uniform pores, lightweight and high pressure resistance.
Patent Information
- Application Number
- CN202510245743.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-04
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-03-04
AI Technical Summary
The existing porous ceramic materials for foam slurry preparation have problems such as low foam stability, large amount of foaming agent, large pore size and complex process.
The high-pressure inflation of micro-nano bubble generator combined with high-speed and strong shearing technology is used to form micro-nanogel foam, and the mineral powder and curing agent are evenly dispersed through high-speed stirring to reduce the use of surfactants and simplify the process flow.
A porous ceramic material with small and uniform pores, lightweight and high compressive strength was obtained. The pore size was distributed between 0.5~23 μm, density was 0.41~0.67 g/cm3, and compressive strength was 16.3~19.1 MPa.
Smart Images

Figure CN119707450A_ABST
Abstract
Description
Technical Field
[0001] The invention discloses a method for preparing a ceramic material, and in particular relates to a method for preparing a porous ceramic with a uniform micro-nano pore size structure, belonging to the technical field of porous ceramics. Background Art
[0002] As a lightweight material, porous ceramics play an important role in related fields such as catalyst carriers, biomaterials, insulation systems and heat exchange due to their high specific surface area, high permeability, low density and high thermal insulation. At present, one of the popular strategies for preparing porous ceramics through liquid slurry is to incorporate the external gas phase into the system through mechanical stirring. Surfactants or mineral colloids are positioned at the gas-liquid interface to stabilize the gas phase; other additives are then used to solidify the foam slurry. There are major obstacles to preparing micronized and lightweight porous foam ceramics by traditional mechanical slurry stirring. The size of the bubbles in the foam slurry plays a vital role in reducing the pore size of the sintered sample. A Chinese patent (publication number: CN101967064A) discloses a method for preparing bulk photocatalytic materials by foaming, which uses egg white as a foaming agent. However, this method uses a large amount of egg white, has low solubility, and causes the foam slurry to be relatively viscous, making it difficult to disperse fine foam in large quantities. A Chinese patent (publication number: CN101941231A) discloses a silicon nitride whisker-bonded silicon carbide porous ceramic and a preparation method thereof, which uses an organic monomer and a cross-linking agent as a gelling agent for stabilizing the foam and solidifying the blank. The method requires a vacuum degree of 6×10 -2 Pa conditions to remove slurry gas, and the presence of oxygen will have an inhibitory effect on the polymerization reaction, these factors increase the complexity of the preparation process. Chinese patent (publication number: CN103145444B) discloses a low-cost method for preparing thermal insulation lightweight porous mullite ceramics, which uses a cationic surfactant dodecyl sulfuric acid as a foaming agent for mullite powder to prepare porous mullite materials under solid content conditions. The foaming agent in this method is easy to produce electrostatic repulsion with mullite powder with negative surface potential, and is easy to desorb during low-temperature drying. The foam layer is difficult to stabilize, and the pore size of the prepared porous ceramics is distributed in about 200~500 μm.
[0003] In summary, the existing methods of preparing porous ceramic materials using foam slurry all have problems such as low foam stability, large amount of foaming agent, large pore size and complex process. Summary of the invention
[0004] In view of the technical drawbacks of the existing foam slurry for preparing porous ceramic materials, the purpose of the present invention is to provide a method for preparing porous ceramics with uniform micro-nano pore sizes. The method uses high-pressure inflation of a micro-nano generator combined with high-speed strong shearing to obtain saturated and stable slurry gel foam, thereby further obtaining a porous ceramic material with small and uniform pores, and the characteristics of light weight and high compressive strength. This method breaks through the limitation of the existing slurry foaming process that requires the use of a high proportion of surfactants and a high solid content to reduce the porosity, reduces the use of surfactants, and has a short process flow, which is easy to operate and meets the requirements of industrial production.
[0005] In order to achieve the above technical objectives, the present invention provides a method for preparing a porous ceramic having uniform micro-nano pore sizes, which comprises the following steps:
[0006] 1) stirring and mixing the gelling agent and the surfactant with water to form a homogeneous solution;
[0007] 2) passing the homogeneous solution into a micro-nano bubble generator for circulation and aeration, and then ejecting to form micro-nano gel foam; the circulation rate is 2-20 L / min; the aeration conditions are: gas flow rate is 100-250 mL / min, and the time is 5-10 min;
[0008] 3) adding mineral powder to the micro-nano gel foam and stirring at a high speed of 1000-1400 r / min for 10-30 min to obtain a slurry gel foam, and then adding a curing agent to the slurry gel foam and stirring at a high speed of 1000-1400 r / min for 15-30 min to obtain a stabilized slurry gel foam;
[0009] 4) The stabilized slurry gel foam is sequentially subjected to injection molding, curing, demoulding, drying and sintering to obtain a porous ceramic material.
[0010] The slurry foaming in the prior art uses shear air as the source of bubbles. Due to the low solubility of air, this is the main reason why it is difficult to achieve micro-nano foaming in the natural environment. The key to the present invention is to use a micro-nano bubble generator to form micro-nano gel foam and use high-speed shear technology to achieve the mixing of mineral powder and micro-nano gel foam, so as to strengthen the uniform dispersion of micro-nano foam in high-viscosity slurry to form stabilized slurry gel foam. More specifically, a homogeneous solution containing a gelling agent and a surfactant is subjected to ultra-high-speed rotation under the action of gas pressure in a micro-nano bubble generator, and then ejected through a nozzle, generating high-speed strong shear and high-frequency pressure changes at the gas-liquid contact interface, forming micro-nano gel foam under artificial extreme conditions, so that the gas content in the gel reaches a supersaturated state, and then mineral powder and a curing agent are added under the shear action of high-speed stirring. While ensuring uniform mixing of the mineral powder, the rapid curing effect of the curing agent is utilized to enable the micro-nano bubbles to be stably and evenly dispersed in the slurry until they are solidified and formed before they aggregate, grow, and dissipate, thereby further miniaturizing and homogenizing the pore size of the porous ceramic, so as to obtain a porous ceramic material having small and uniform pores, and having the characteristics of lightweight and high compressive strength.
[0011] Another innovation of the present invention is that: first, a slurry gel foam in which micro-nano foams are uniformly dispersed is formed by using a gelling agent, a surfactant and a mineral powder, and then a curing agent is introduced for stabilization. If the curing agent is introduced in advance, it will affect the gelling effect of the micro-nano foam, making it difficult to form a uniform and stable gel network, resulting in uneven pore wall thickness, which is not conducive to the forming of a porous ceramic body and greatly reduces the strength of the porous ceramic. After the slurry gel foam is prepared first, a curing agent is introduced to utilize the rapid curing effect of the curing agent so that the micro-nano bubbles can be stably and uniformly dispersed in the slurry until they are cured and formed before they aggregate, grow and dissipate, thereby obtaining a porous ceramic material with small and uniform pores, light weight and high compressive strength.
[0012] As a preferred solution, the surfactant includes at least one of sodium dodecyl sulfate, dodecylamine, hexadecyl methylammonium bromide and plant protein. The plant protein is further preferably tea saponin or soapberry triterpenoid saponin. The surfactants selected in the present invention are all commercially available industrial pure or analytically pure. They are conventional surfactants in the process of preparing porous ceramic materials from foam slurry. The type of surfactant will affect the gas-liquid-solid distribution characteristics, and the preferred surfactant is conducive to strengthening the uniform dispersion of micro-nano bubbles and mineral powder.
[0013] As a preferred solution, the gelling agent comprises at least one of carboxymethyl cellulose, soluble starch and sodium alginate. The gelling agents selected in the present invention are all commercially available industrial pure or analytical pure.
[0014] As a preferred solution, the curing agent includes at least one of polyvinyl alcohol, polyvinyl ether, isobutylene-maleic anhydride copolymer and polyacrylate. The curing agents selected in the present invention are all commercially available industrial pure or analytically pure. The gas-liquid-solid interfacial tension can be controlled by the preferred types of gelling agent and curing agent, which is conducive to controlling the micro-nano bubbles to be stably and uniformly dispersed in the slurry before aggregation, growth and dissipation until the green body is solidified.
[0015] As a preferred solution, the particle size of the mineral powder is distributed in 400-1000 meshes, and the Al2O3 content is 10-44wt%, and the SiO2 content is 15-60wt%. As a more preferred solution, the mineral powder includes at least one of coal gangue, coal slime, red mud, lithium slag, kaolin, mullite, feldspar, quartz, copper tailings, iron tailings and lead-zinc tailings.
[0016] As a preferred solution, the mass ratio of the gelling agent and the surfactant to the water is (0.005-0.03): (0.002-0.015): 1. The amount of gelling agent and surfactant used affects the bubble and foam dispersion effect. If the gelling agent ratio is too high and / or the surfactant content is too low, the foaming effect is affected, resulting in a low porosity of the ceramic; if the surfactant content is too high, large bubbles are easily formed and easily aggregated, and micro-nano bubbles and uniformly dispersed micro-nano pores cannot be formed, and the porous ceramic has low strength. If the gelling agent ratio is too low, the micro-nano pores are difficult to maintain stably. The gelling agent and surfactant of the present invention are fully dissolved in an appropriate amount of water in advance and then added during the addition process.
[0017] As a preferred solution, the mass ratio of the mineral powder to the micro-nano gel foam is (0.6-1.2): 1. The quality of the mineral powder mainly affects the density and porosity of the ceramic. If the introduction ratio of the mineral powder is too high, the porous ceramic formed has a low porosity and a large density, the pores are not uniform and abundant, and the thermal insulation and sound insulation properties are poor; if the ratio is too low, the structure is easy to collapse during the curing process and is difficult to form, and the porous ceramic pore wall after firing has a weak solid phase connection and low strength.
[0018] As a preferred solution, the mass ratio of the curing agent to the slurry gel foam is (0.06-0.30):1. If the curing agent ratio is too high, the micro-nano pore structure will be destroyed and the cost will be greatly increased; if the ratio is too low, the fluidity and stability of the slurry will deteriorate during injection molding, the slurry is prone to agglomeration or precipitation, and defects are easily formed after the green body is demolded. The curing agent is measured by its dry basis mass.
[0019] As a preferred solution, the curing conditions are: curing at a temperature of 30-80°C for 8-24 hours.
[0020] As a preferred solution, the drying conditions are: drying at a temperature of 100-120° C. for 1-3 hours.
[0021] As a preferred solution, the sintering conditions are: sintering at a temperature of 1250-1400°C for 0.5-2 h.
[0022] The gelling agent involved in the present invention is added in the form of a solution. The gelling agent is mixed with deionized water in a mass ratio of (0.005-0.03):1, and stirred with magnetic force in a water bath to form a homogeneous solution.
[0023] The surfactant involved in the present invention is added in the form of a solution. The surfactant and deionized water are mixed in a mass ratio of (0.001-0.02):1, and stirred with magnetic force in a water bath to form a homogeneous solution.
[0024] The curing agent involved in the present invention is added in the form of a solution. The curing agent and deionized water are mixed in a mass ratio of (0.0125-0.04):1, and stirred with magnetic force in a water bath to form a homogeneous solution.
[0025] The temperature of the water bath magnetic stirring involved in the present invention is 30-45° C., and the stirring speed is 200-500 r / min.
[0026] Compared with the prior art, the technical solution of the present invention has the following positive effects:
[0027] (1) The present invention uses a micro-nano bubble generator to generate micro-nano gel foam, thereby enhancing the uniform dispersion of micro-bubbles in high-viscosity slurry, making the pore size of the formed porous ceramics further refined and uniform. The micro-nano porous ceramics are prepared using a micro-nano bubble generator, breaking through the limitation of the slurry foaming process that uses a high proportion of surfactants and a high solid content to reduce the porosity, and reducing the use of surfactants.
[0028] (2) The present invention uses micro-nano gel foam as the base liquid, which is suitable for the selection of various mineral powders and has good universality.
[0029] (3) The porous ceramics prepared by the present invention have small and uniform pores, and are lightweight and have high compressive strength. The pore size distribution is 0.5-23 μm, and the density is 0.41-0.67 g / cm 3 , compressive strength 16.3~19.1 MPa.
[0030] (4) The method for preparing porous ceramics of the present invention has a short process, is easy to operate, and meets the requirements of industrial production.
[0031] In summary, the process for preparing porous ceramic materials provided by the present invention adjusts the pore structure by changing the foam generation method, has the characteristics of short process and easy operation, and can obtain porous ceramic materials with small and uniform pores, light weight and high compressive strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is the SEM image of the micro-nano porous ceramic prepared in Example 1.
[0033] Figure 2 This is a comparison chart of the micro-nano gel foam prepared in Example 1 and water foaming. DETAILED DESCRIPTION
[0034] The present invention is further described in detail below with reference to specific examples, which does not limit the protection scope of the claims.
[0035] In the following specific implementations:
[0036] The gelling agent, surfactant and curing agent are industrial pure or analytical pure.
[0037] Example 1
[0038] Step 1: Add the gelling agent into deionized water at a mass ratio of carboxymethyl cellulose to deionized water of 0.015:1, stir magnetically in a water bath to form a dispersed homogeneous solution for standby use;
[0039] Step 2: Add the surfactant to deionized water at a mass ratio of hexadecyl methylammonium bromide to deionized water of 0.001:1, stir magnetically in a water bath to form a dispersed homogeneous solution for standby use;
[0040] Step 3: Add the curing agent to deionized water at a mass ratio of polyvinyl alcohol to deionized water of 0.0125:1, stir magnetically in a water bath to form a dispersed homogeneous solution for standby use;
[0041] Step 4: Carboxymethyl cellulose solution, hexadecyl methylammonium bromide solution and appropriate amount of deionized water are mixed at a mass ratio of carboxymethyl cellulose: hexadecyl methylammonium bromide: deionized water of 0.008:0.002:1 (total amount of water), and the aqueous solution containing gelling agent and surfactant is passed into a micro-nano bubble generator at a circulation rate of 10 L / min, a circulation flow time of 5 min, an inflation gas flow rate of 100 mL / min, and a micro-nano gel foam is obtained after spraying;
[0042] Step 5: According to the mass ratio of gangue powder to micro-nano gel foam of 0.6:1, a high-speed stirrer is used for secondary stirring, and the stirring is carried out at 1400r / min for 10min. The Al2O3 content of the gangue powder is 39wt%, the SiO2 content is 50wt%, the other components are 11wt%, and the average particle size is 600 mesh;
[0043] Step 6: adding polyvinyl alcohol to the foamed ore slurry at a mass ratio of polyvinyl alcohol (measured on a dry basis) to ore slurry gel foam of 0.06:1, and stirring at a high speed of 1200 r / min for 15 min to obtain a stabilized ore slurry gel foam;
[0044] Step 7: inject the stabilized mineral pulp gel foam slurry into a mold, cure it at 60° C. for 12 hours, and demould to obtain a porous material body;
[0045] Step 8, drying the porous material body at 100° C. for 2 h, and sintering at 1400° C. for 0.5 h to obtain a porous ceramic micro-nano material;
[0046] The pore size of the sintered sample is distributed in the range of 0.9~25μm, and the density is 0.48g / cm 3 , the compressive strength is 19.1MPa.
[0047] Example 2
[0048] Step 1: add the gelling agent into deionized water at a mass ratio of carboxymethyl cellulose to deionized water of 0.02:1, stir magnetically in a water bath to form a dispersed homogeneous solution for standby use;
[0049] Step 2: Add the surfactant to deionized water at a mass ratio of dodecylamine to deionized water of 0.0015:1, stir magnetically in a water bath to form a dispersed homogeneous solution for standby use;
[0050] Step 3: Add the curing agent to deionized water at a mass ratio of polyacrylate to deionized water of 0.02:1, stir magnetically in a water bath to form a dispersed homogeneous solution for standby use;
[0051] Step 4: Carboxymethyl cellulose solution, dodecylamine solution and appropriate amount of deionized water are mixed at a mass ratio of carboxymethyl cellulose: dodecylamine: deionized water of 0.008:0.002:1 (total amount of water), and the aqueous solution containing gelling agent and surfactant is passed into a micro-nano bubble generator at a circulation flow rate of 15 L / min, a circulation flow time of 5 min, and an inflation gas flow rate of 200 mL / min, and micro-nano gel foam is obtained after spraying;
[0052] Step 5: According to the mass ratio of lithium slag powder to micro-nano gel foam of 0.6:1, a high-speed stirrer is used for secondary stirring, and stirring is carried out at 1400 r / min for 10 min; the lithium slag powder has an Al2O3 content of 21 wt%, a SiO2 content of 57 wt%, other components of 22 wt%, and an average particle size of 700 mesh;
[0053] Step 6: adding polyacrylate to the slurry gel foam at a mass ratio of polyacrylate (measured on a dry basis): slurry gel foam of 0.08:1, and stirring at a high speed of 1200 r / min for 15 min to obtain stabilized slurry gel foam;
[0054] Step 7: inject the stabilized slurry gel foam into a mold, cure it at 60° C. for 12 hours, and demould to obtain a porous material body;
[0055] Step 8, drying the porous material body at 100° C. for 2 h, and sintering at 1250° C. for 0.5 h to obtain a porous ceramic micro-nano material;
[0056] The pore size of the sintered sample is distributed in the range of 1~23μm, and the density is 0.41g / cm 3 , the compressive strength is 16.3MPa.
[0057] Example 3
[0058] Step 1: Add the gelling agent into deionized water at a mass ratio of carboxymethyl cellulose to deionized water of 0.03:1, stir magnetically in a water bath to form a dispersed homogeneous solution for standby use;
[0059] Step 2: Add surfactant to deionized water at a mass ratio of 0.02:1 of tea saponin to deionized water, stir magnetically in a water bath to form a dispersed homogeneous solution for standby use;
[0060] Step 3: Add the curing agent to deionized water at a mass ratio of polyvinyl alcohol to deionized water of 0.04:1, stir magnetically in a water bath to form a dispersed homogeneous solution for standby use;
[0061] Step 4: Carboxymethyl cellulose solution, tea saponin solution and appropriate amount of deionized water are mixed at a mass ratio of carboxymethyl cellulose: tea saponin: deionized water of 0.008:0.002:1 (total amount of water), and the aqueous solution containing gelling agent and surfactant is passed into a micro-nano bubble generator at a circulation flow rate of 8 L / min, a circulation flow time of 10 min, an inflation gas flow rate of 250 mL / min, and a micro-nano gel foam is obtained after spraying;
[0062] Step 5: The mass ratio of coal sludge powder to micro-nano gel foam is 0.6:1, and secondary stirring is performed using a high-speed stirrer at 1400 r / min for 30 min. The coal sludge powder has an Al2O3 content of 25 wt%, a SiO2 content of 47 wt%, other components of 28 wt%, and an average particle size of 1000 mesh;
[0063] Step 6: adding polyvinyl alcohol to the slurry gel foam at a mass ratio of polyvinyl alcohol to slurry gel foam of 0.08:1, and stirring at a high speed of 1200 r / min for 15 min to obtain a stabilized slurry gel foam;
[0064] Step 7: inject the stabilized slurry gel foam into a mold, cure it at 60° C. for 12 h, and demould to obtain a porous material body;
[0065] Step 8, drying the porous material body at 100° C. for 2 h, and sintering at 1400° C. for 0.5 h to obtain a porous ceramic micro-nano material;
[0066] The pore size of the sintered sample is distributed in the range of 0.5~17μm, and the density is 0.67g / cm 3 , the compressive strength is 17.7MPa.
[0067] Comparative Example 1
[0068] The other operating conditions and implementation steps were the same as those in Example 1, except that a common stirrer was used in place of the micro-nano bubble generator in step 4. The gel foam was obtained by high-speed stirring at 1400 r / min for 10 min. The pore size distribution of the calcined sample was in the range of 93-463 μm, and the density was 0.78 g / cm 3 , and the compressive strength is 5.47 MPa. The bubbles formed by ordinary agitators have large diameters and low density, which leads to large and uneven pore size and low compressive strength of the fired porous ceramics.
[0069] Comparative Example 2
[0070] The other operating conditions and implementation steps are the same as those in Example 2, except that the amount of gelling agent added is reduced in step 4, and the mass ratio of carboxymethyl cellulose: dodecylamine: deionized water is 0.002:0.002:1. The pore size distribution of the calcined sample is in the range of 70-325 μm, and the density is 0.70 g / cm 3 , and the compressive strength is 7.31MPa. Due to the low proportion of gelling agent, the micro-nano foam is difficult to maintain stability during the curing process, part of the micro-nano pore structure collapses, and the pore distribution is uneven.
[0071] Comparative Example 3
[0072] The other operating conditions and implementation steps are the same as those in Example 3, except that the curing agent addition step and method are changed. The gelling agent, surfactant, and curing agent are added to water at the same time to prepare a mixed homogeneous solution. The pore size distribution of the fired sample is in the range of 125-645 μm, and the density is 0.59 g / cm 3 , and the compressive strength is 3.86 MPa. The simultaneous mixing of the three agents affects the gelling effect of the micro-nano foam slurry, and a uniform and stable gel network cannot be formed. The pore wall thickness is uneven, which is not conducive to the forming of the porous ceramic body and the strength is greatly reduced.
Claims
1. A method for preparing a porous ceramic with uniform micro-nano pore size, characterized in that: The following steps are involved: 1) stirring and mixing the gelling agent and the surfactant with water to form a homogeneous solution; 2) passing the homogeneous solution into a micro-nano bubble generator for circulation and aeration, and then ejecting to form micro-nano gel foam; the circulation rate is 2-20 L / min; the aeration conditions are: gas flow rate is 100-250 mL / min, and the time is 5-10 min; 3) adding mineral powder to the micro-nano gel foam and stirring at a high speed of 1000-1400 r / min for 10-30 min to obtain a slurry gel foam, and then adding a curing agent to the slurry gel foam and stirring at a high speed of 1000-1400 r / min for 15-30 min to obtain a stabilized slurry gel foam; 4) The stabilized slurry gel foam is sequentially subjected to injection molding, curing, demoulding, drying and sintering to obtain a porous ceramic material.
2. The method for preparing a porous ceramic having uniform micro-nano pore size according to claim 1, characterized in that: The gelling agent comprises at least one of carboxymethyl cellulose, soluble starch and sodium alginate; and / or, The surfactant comprises at least one of sodium dodecyl sulfonate, dodecylamine, hexadecyl methylammonium bromide and plant protein; and / or, The curing agent includes at least one of polyvinyl alcohol, polyvinyl ether, isobutylene-maleic anhydride copolymer and polyacrylate; and / or, The particle size of the mineral powder is distributed in the range of 400-1000 meshes, and the Al2O3 content is 10-44wt%, and the SiO2 content is 15-60wt%.
3. The method for preparing a porous ceramic having uniform micro-nano pore size according to claim 1 or 2, characterized in that: The mass ratio of the gelling agent and the surfactant to the water is (0.005-0.03): (0.002-0.015):
1.
4. The method for preparing a porous ceramic having uniform micro-nano pore size according to claim 1 or 2, characterized in that: The mass ratio of the mineral powder to the micro-nano gel foam is (0.6-1.2):
1.
5. The method for preparing a porous ceramic having uniform micro-nano pore size according to claim 1 or 2, characterized in that: The mass ratio of the curing agent to the slurry gel foam is (0.06-0.30):
1.
6. The method for preparing a porous ceramic having uniform micro-nano pore sizes according to claim 2, characterized in that: The mineral powder includes at least one of coal gangue, coal slime, red mud, lithium slag, kaolin, mullite, feldspar, quartz, copper tailings, iron tailings and lead-zinc tailings.
7. The method for preparing a porous ceramic having uniform micro-nano pore sizes according to claim 1, characterized in that: The curing conditions are: curing at a temperature of 30-80° C. for 8-24 hours.
8. The method for preparing a porous ceramic with uniform micro-nano pore size according to claim 1, characterized in that: The drying conditions are: drying at a temperature of 100-120° C. for 1-3 hours.
9. The method for preparing a porous ceramic with uniform micro-nano pore size according to claim 1, characterized in that: The sintering conditions are: sintering at a temperature of 1250-1400° C. for 0.5-2 hours.
Citation Information
Patent Citations
Gel injection molding technology of large-sized and complicated-shape silicon carbide ceramic biscuit
CN101941231A
Protein foaming method for preparing porous ceramics composite material
CN101967064A
Method for preparing heat-insulation lightweight porous mullite ceramic at low cost
CN103145444B
Method for preparing heat-insulation lightweight porous mullite ceramic at low cost
CN103145444A
Additive, preparation method thereof and concrete
CN114620969A
Cited By
Method for epiphytic planting of dendrobium officinale through southern magnolia
CN121773946A